A super-hydrophobic-super-hydrophilic Janus copper foam evaporator and its preparation method and application

By spraying a mixed solution of PDMS, nano-vaporous silica and nanocarbon black on the foam copper surface, a superhydrophobic-super hydrophilic Janus foam copper evaporator was prepared, solving the problems of low evaporation rate and lack of self-cleaning function of existing interface materials, and achieving the sustainability of efficient water evaporation and seawater desalination.

CN115926756BActive Publication Date: 2025-03-11JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211673028.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-03-11
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

The existing interface materials used in seawater desalination evaporators have low evaporation rate, poor mechanical stability, and do not have the function of self-cleaning of salt crystals.

Method used

A superhydrophobic-super hydrophilic Janus foam copper evaporator is used, which forms a material with extremely high light-absorbing and heat-absorbing properties and floating properties by spraying a mixed solution of PDMS, nano-vapor-phase silica and nanocarbon black on the surface of the foam copper.

Benefits of technology

It achieves efficient water evaporation, with an evaporation rate of 1.04kg·m-2, an evaporation efficiency of 83.2%, and has good salt resistance and self-cleaning function, which is suitable for seawater desalination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926756B_ABST
    Figure CN115926756B_ABST
Patent Text Reader

Abstract

The invention relates to a super-hydrophobic-super-hydrophilic Janus copper foam evaporator and a preparation method and application thereof, comprising: (1) pre-spraying solution: mixing PDMS, nano-gas phase silica and nano-carbon material in proportion, adding an organic solvent to dilute, and stirring to obtain a pre-spraying solution; (2) adding an adhesive to the pre-spraying solution and mixing to obtain a spraying solution; (3) spraying the spraying solution onto one surface of a clean copper foam, taking measures before spraying to prevent the spraying solution from penetrating into another surface through the pores of the copper foam during the spraying process, selectively and repeatedly spraying the spraying solution after the spraying surface is dried, and obtaining a super-hydrophobic-super-hydrophilic Janus copper foam evaporator after thermal curing; the evaporator has excellent light absorption and heat absorption characteristics and stable floatation; has good evaporation performance and salt rejection ability, and the evaporation channel will not be blocked by deposited salt crystals, and can be used for a long time in seawater desalination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of interface treatment, and in particular to a super-hydrophobic-super-hydrophilic Janus copper foam evaporator and a preparation method and application thereof. Background Art

[0002] Existing desalination technologies have many disadvantages, such as low thermal efficiency, high energy consumption, high operating costs, and greenhouse gas emissions, which limit their application. Solar evaporation technology is considered to be one of the most promising technologies for producing fresh water. However, traditional solar desalination technology has high construction and maintenance costs, low fresh water production, and high dependence on incident light. Therefore, many new types of solar evaporators have emerged in recent years. Traditional direct solar desalination focuses on heating the entire water body rather than the surface interface of the water body, and has low efficiency. Recently, with the further study of solar evaporation by researchers, based on the phenomenon that evaporation takes place on the surface of the liquid, an interfacial thermal evaporation technology that directly heats the air-liquid interface has been proposed.

[0003] The inspiration of Janus interfacial photothermal evaporation material comes from lotus leaves in nature. Its dual wettability of super hydrophilic bottom and super hydrophobic surface provides it with stability and self-floating ability in water, which can meet the needs of interfacial thermal evaporation. One of the most important characteristics of interfacial thermal evaporation technology is its wettability. The super hydrophobicity of the surface and the super hydrophilicity of the bottom determine its water transport, light absorption, device floatation and stability. The principle of Janus interfacial thermal evaporation technology is that the photothermal material absorbs sunlight and converts it into internal energy. Due to the heat conduction effect, the energy is transferred to the air-water interface with a lower temperature. Water absorbs heat and evaporates. After gasification, water vapor escapes from the pores of the material. Since the hydrophobic layer of the material has low water affinity, the diffusion and escape of water vapor are faster. The evaporation process occurs on the surface of the liquid, and the hydrophobic layer can make the entire evaporator float on the water surface, reducing the heat loss caused by thermal radiation, etc. Janus material is a reasonable choice as an interfacial thermal evaporator.

[0004] One of the main reasons why the application of Janus materials in solar evaporation technology has not been promoted is that the price of hydrophobic photothermal materials is relatively expensive, the preparation process is complicated, the evaporation efficiency is not high, and there is a problem of salt deposition during the evaporation process. As the desalination process proceeds, salt crystals will accumulate on the surface of the evaporation material, blocking the outlet for the rising steam. As the salt crystals are deposited in large quantities, the solar energy absorption rate on the surface of the photothermal material will also be affected. Therefore, the development of solar interface evaporation materials with high evaporation rate, strong mechanical stability and salt crystal self-cleaning ability is of extraordinary significance for achieving breakthroughs in sustainable and efficient water evaporation and desalination technology. Summary of the invention

[0005] In order to solve the technical problems of low evaporation rate, poor mechanical stability and lack of salt crystallization self-cleaning function of interface materials currently used in seawater desalination evaporators, a super-hydrophobic-super-hydrophilic Janus copper foam evaporator and its preparation method and application are provided. The evaporator of the present invention has a super-hydrophobic-super-hydrophilic Janus interface, a high water evaporation rate and good salt rejection ability, and can be applied in the field of seawater desalination evaporation.

[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0007] A method for preparing a super-hydrophobic-super-hydrophilic Janus copper foam evaporator comprises the following steps:

[0008] (1) Pre-spraying solution: PDMS, nano-fumed silica and nano-carbon material are mixed in proportion, diluted with an organic solvent, and stirred to obtain a pre-spraying solution;

[0009] (2) adding a binder to the pre-spraying solution and mixing evenly to obtain a spraying solution;

[0010] (3) Spraying the spray solution onto one surface of a clean copper foam. Before spraying, measures need to be taken to prevent the spray solution from penetrating into another surface through the pores of the copper foam during the spraying process. After the sprayed surface is dried, the spray solution can be selectively sprayed repeatedly for multiple times. After thermal curing, a super-hydrophobic-super-hydrophilic Janus copper foam evaporator is obtained.

[0011] Furthermore, the PDMS is a mixture of a PDMS prepolymer and a PDMS curing agent in a mass ratio of 10:1; the nano-carbon material is any one or more of nano-carbon black, graphene, graphene oxide, and carbon nanotubes; and the organic solvent is hexane.

[0012] Furthermore, the mass ratio of the PDMS, the nano-gas-phase silica, and the nano-carbon material is 10:1:5.

[0013] Furthermore, the particle size of the nano-gas-phase silicon dioxide is 20-50 nm, the particle size of the nano-carbon material is 200-500 nm; and the pore size of the foam copper is 30-50 μm.

[0014] Furthermore, the mass concentration of the pre-spraying solution is 0.05-0.18 g / mL.

[0015] Furthermore, the measure is to extrude the copper foam into the soft fiber so that only one surface thereof is exposed to the outside, or the measure is to seal the holes of the copper foam surface that does not need to be sprayed with adhesive tape.

[0016] Furthermore, the adhesive is tetraethyl orthosilicate containing a catalyst, and the volume ratio of the catalyst to the tetraethyl orthosilicate is 1:1; and the catalyst is dibutyltin dilaurate.

[0017] Furthermore, the volume ratio of the pre-spraying solution to the adhesive is (45-150):1.

[0018] Furthermore, the thermal curing temperature is 80-120° C. and the curing time is 2-6 hours.

[0019] Another aspect of the present invention provides a super-hydrophobic-super-hydrophilic Janus copper foam evaporator prepared by the above preparation method.

[0020] The last aspect of the present invention provides the use of the super-hydrophobic-super-hydrophilic Janus copper foam evaporator prepared by the above preparation method in seawater desalination evaporation.

[0021] Beneficial technical effects:

[0022] The present invention adds carbon black and silicon dioxide to a polymethylsiloxane PDMS solution in sequence, uniformly stirs, and then ultrasonically vibrates to spray the solution on the surface of the foam copper, and then puts the solution into an oven for thermal curing to obtain a super-hydrophobic-super-hydrophilic Janus foam copper evaporator. The Janus foam copper evaporator prepared by the present invention has a simple preparation process, is easy to implement, and has low cost, overcomes the problem of complex laboratory processes, and can be applied to the field of seawater desalination evaporation.

[0023] The super-hydrophobic-super-hydrophilic Janus copper foam evaporator of the present invention has excellent light absorption and heat absorption characteristics, excellent floating performance, and can stably float on the water surface. The super-hydrophobic-super-hydrophilic Janus copper foam evaporator has excellent solar evaporation performance. Under one sun, the evaporation rate reaches 1.04kg·m -2 , the evaporation efficiency reaches 83.2%. It has good stability, and is resistant to low and high temperature changes and UV radiation. It has excellent salt rejection ability, and the evaporation channel will not be blocked by deposited salt crystals, and can be used for a long time in seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 a is a floating effect diagram of the super hydrophobic-super hydrophilic Janus copper foam evaporator of Example 1;

[0025] Figure 1 b is a water contact angle diagram of the spraying surface of the super hydrophobic-super hydrophilic Janus foam copper evaporator of Example 1;

[0026] Figure 1 c is a water contact angle diagram of the uncoated surface of the superhydrophobic-superhydrophilic Janus copper foam evaporator of Example 1;

[0027] Figure 1 d is a schematic diagram of the water evaporation process of the superhydrophobic-superhydrophilic Janus copper foam evaporator of Example 1.

[0028] Figure 2 This is a scanning electron microscope image of the super-hydrophobic-super-hydrophilic Janus copper foam evaporator of Example 1 before and after spraying.

[0029] Figure 3 This is a graph showing the cyclic high and low temperature resistance and cyclic UV radiation resistance of the superhydrophobic-superhydrophilic Janus copper foam evaporator of Example 1.

[0030] Figure 4 This is a graph of the evaporation rate of the superhydrophobic-superhydrophilic Janus copper foam evaporator of Example 1 under different light intensities.

[0031] Figure 5 This is a diagram of the self-cleaning and desalting ability of the superhydrophobic-superhydrophilic Janus copper foam evaporator during the evaporation process of Example 1. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0033] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0034] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.

[0035] The PDMS used below is a mixture of PDMS prepolymer and PDMS curing agent in a mass ratio of 10:1, such as SYLGARD 184 SILICONE ELASTOMER potting glue from Dow Corning.

[0036] Example 1

[0037] A method for preparing a super-hydrophobic-super-hydrophilic Janus copper foam evaporator comprises the following steps:

[0038] Sample pretreatment: 5cm×5cm copper foam was selected as the substrate, the pore size of the copper foam was about 30-50μm, and it was cleaned with acetone, alcohol, and deionized water under ultrasonic conditions for 30min, and then dried for use;

[0039] (1) Pre-spraying solution: 1.0 g PDMS, 0.1 g nano-fumed silica (20-50 nm) and 0.5 g nano-carbon black (200-500 nm) were mixed, 30 mL hexane was added for dilution, and stirred for 30 min to obtain a uniform black pre-spraying solution;

[0040] (2) adding 0.1 mL of ethyl orthosilicate and 0.1 mL of dibutyltin dilaurate to the pre-spraying solution, stirring evenly and ultrasonically shaking for 30 min to obtain a spraying solution;

[0041] (3) In order to prevent the spray solution from penetrating into another surface through the pores of the copper foam during the spraying process, the copper foam needs to be squeezed into a soft fiber (such as sponge or cotton) before spraying so that only one surface of the copper foam is exposed to the air. The spray solution is sprayed onto the exposed surface of the copper foam, and the copper foam is placed in an oven at 80° C. for thermal curing for 6 h to obtain a superhydrophobic-superhydrophilic Janus copper foam evaporator.

[0042] Example 2

[0043] A method for preparing a super-hydrophobic-super-hydrophilic Janus copper foam evaporator comprises the following steps:

[0044] Sample pretreatment: 5cm×5cm copper foam was selected as the substrate, the pore size of the copper foam was about 30-50μm, and it was cleaned with acetone, alcohol, and deionized water under ultrasonic conditions for 30min, and then dried for use;

[0045] (1) Pre-spraying solution: 5.0 g PDMS, 0.5 g nano-fumed silica (20-50 nm) and 2.5 g nano-carbon black (200-500 nm) were mixed, 60 mL hexane was added for dilution, and stirred for 30 min to obtain a uniform black pre-spraying solution;

[0046] (2) adding 0.5 mL of ethyl orthosilicate and 0.5 mL of dibutyltin dilaurate to the pre-spraying solution, stirring evenly and ultrasonically shaking for 30 min to obtain a spraying solution;

[0047] (3) In order to prevent the spray solution from penetrating into another surface through the pores of the copper foam during the spraying process, the copper foam needs to be squeezed into a soft fiber (such as sponge or cotton) before spraying so that only one surface of the copper foam is exposed to the air. The spray solution is sprayed onto the exposed surface of the copper foam. After the sprayed surface is dried, the spray solution is sprayed twice, and then the surface is placed in an oven for thermal curing at 100° C. for 4 h to obtain a superhydrophobic-superhydrophilic Janus copper foam evaporator.

[0048] Example 3

[0049] A method for preparing a super-hydrophobic-super-hydrophilic Janus copper foam evaporator comprises the following steps:

[0050] Sample pretreatment: 5cm×5cm copper foam was selected as the substrate, the pore size of the copper foam was about 30-50μm, and it was cleaned with acetone, alcohol, and deionized water under ultrasonic conditions for 30min, and then dried for use;

[0051] (1) Pre-spraying solution: 10.0 g PDMS, 1.0 g nano-fumed silica (20-50 nm) and 5.0 g nano-carbon black (200-500 nm) were mixed, 90 mL hexane was added for dilution, and stirred for 30 min to obtain a uniform black pre-spraying solution;

[0052] (2) adding 0.5 mL of ethyl orthosilicate and 0.5 mL of dibutyltin dilaurate to the pre-spraying solution, stirring evenly and ultrasonically shaking for 30 min to obtain a spraying solution;

[0053] (3) In order to prevent the spray solution from penetrating into another surface through the pores of the copper foam during the spraying process, one surface of the copper foam was sealed with tape before spraying, and the above-mentioned spray solution was sprayed on the surface of the copper foam that was not adhered with tape. After the sprayed surface was dried, the spray solution was repeatedly sprayed three times, and then placed in an oven at 120°C for thermal curing for 2 hours to obtain a superhydrophobic-superhydrophilic Janus copper foam evaporator.

[0054] Comparative Example 1

[0055] The preparation method of the Janus copper foam evaporator of this comparative example is the same as that of Example 1, except that the pre-spraying solution in step 1 contains only PDMS.

[0056] Comparative Example 2

[0057] The preparation method of the Janus copper foam evaporator of this comparative example is the same as that of Example 1, except that the pre-spraying solution in step 1 contains only PDMS and nano-fumed silica.

[0058] Comparative Example 3

[0059] The preparation method of the Janus copper foam evaporator of this comparative example is the same as that of Example 1, except that the pre-spraying solution in step 1 contains only PDMS and nano carbon black.

[0060] Comparative Example 4

[0061] The preparation method of the Janus copper foam evaporator of this comparative example is the same as that of Example 1, except that step 2 does not exist, and the pre-spraying solution is directly sprayed on the copper foam.

[0062] Example 4

[0063] The water contact angle of the sprayed surface of the products of the above embodiments and comparative examples was tested, and the results are shown in Table 1 below.

[0064] Table 1 Water contact angle of Janus copper foam evaporator of embodiment and comparative example

[0065]

[0066] As can be seen from Table 1, Comparative Example 1 has a surface with only PDMS, Comparative Example 2 has a surface with PDMS+nano-fumed silica, and Comparative Example 3 has a surface with PDMS+carbon black, all of which have a certain hydrophobicity, and the effects of nano-fumed silica and nano-carbon black are basically equivalent; and the present invention sprays a mixed solution of carbon black and nano-fumed silica wrapped in PDMS on the upper surface of the foam copper, so that the sprayed surface of the Janus copper foam evaporator prepared has super hydrophobicity, and the water contact angle is greater than 160°, and the unsprayed surface has super hydrophilicity, and the water contact angle is close to 0°.

[0067] The Janus copper foam evaporator of Example 1 has the ability to float like a lotus leaf. The excellent super-hydrophobic water-repellent property of the sprayed surface provides it with a stable floating ability. The floating effect is shown in FIG. Figure 1 . Figure 1 The Janus copper foam evaporator that floats in a is the floating effect obtained after its unsprayed lower surface is in contact with water; the one that sinks in the water is the untreated copper foam. Figure 1 b is the water contact angle diagram of the sprayed surface, Figure 1 c is the water contact angle diagram of the unsprayed surface, Figure 1 Figure d is a schematic diagram of the water evaporation process in the evaporator.

[0068] The scanning electron microscope images of the Janus copper foam evaporator of Example 1 before and after spraying are as follows: Figure 2 As shown. Figure 2 It can be seen that the surface of the three-dimensional pore structure in the foam copper raw material is relatively smooth and flat (such as Figure 2a1~a3, the magnification ratio of a1~a3 gradually increases, and the scale lengths are 200μm, 100μm, and 20μm respectively. The structure is hydrophilic due to the capillary phenomenon; after spraying and curing on its surface, a large number of micro-nano spherical protrusions appear on the surface of the three-dimensional pore structure (such as Figure 2 In b1-b3, the magnification ratio of b1-b3 gradually increases, and the scale length is 200μm, 100μm, and 20μm respectively. The protrusions are microparticles formed by the aggregation of carbon black and silicon dioxide. These lotus leaf-like papillary structures provide the necessary micro-nano rough structures for forming super-hydrophobicity, and the PDMS that attaches these particles to the foam copper fiber also provides lower surface energy. Therefore, a super-hydrophobic surface is formed on the sprayed surface, while the unsprayed surface is the original copper mesh surface, which is a super-hydrophilic surface.

[0069] The Janus copper foam evaporator of Example 1 was subjected to cyclic high and low temperature resistance test and cyclic ultraviolet radiation resistance test. Each cycle of temperature change was from -40°C to 100°C, and each cycle of ultraviolet radiation resistance was 100h. The test results are shown in Figure 3 .Depend on Figure 3 It can be seen that after 10 high and low temperature cycles from -40℃ to 100℃ and 10 100h UV irradiation cycles, the sprayed surface of the Janus foam copper evaporator is still a superhydrophobic surface, and the water contact angle is still greater than 150°, which has good stability.

[0070] The sprayed surfaces of the Janus copper foam evaporators of other embodiments have the same stability effect. The stability of each embodiment and comparative example is shown in Table 2.

[0071] Table 2 Water contact angle of the sprayed surface of the embodiment and comparative example products after 10 cycles of high and low temperature resistance and UV radiation resistance

[0072]

[0073] It can be seen from Table 2 that although the initial water contact angle of the surface of Comparative Example 4 has good superhydrophobicity, it is because no tetraethyl orthosilicate is added during the preparation process, and the initial superhydrophobic surface is reduced to a hydrophobic surface of less than 120°. It can be seen that the water contact angle of the surface of the comparative example 4 decreases significantly after 10 cycles of high and low temperature resistance and ultraviolet radiation resistance, and the stability of the comparative example 4 is poor, which is due to the poor adhesion of the coating on the surface of the foam copper.

[0074] The Janus copper foam evaporator of Example 1 was tested for evaporation rate, and the results are shown in Figure 4 The water evaporation rate of Janus copper foam was measured under the conditions of room temperature of 25℃ and relative humidity of 40% under the conditions of direct sunlight of different powers. The evaporation rates of Janus copper foam were 1.04kgm-1 and 1.06kgm-1 respectively when the light intensity was 1W, 3W and 5W.-2 、2.85kgm -2 and 5.49kgm -2 The evaporation rates of the above examples and comparative examples are shown in Table 3.

[0075] Table 3 Evaporation rate of the products of the embodiments and comparative examples

[0076]

[0077] As shown in Table 3, although the surface of Comparative Example 4 initially has good superhydrophobicity, its stability is poor, so the water evaporation rate and evaporation efficiency are worse than those of Example 1 at a light intensity of 1W. Since there is no carbon black in Comparative Examples 1 and 2, the evaporation effect of the two surfaces on water is small, and although Comparative Example 3 has carbon black, compared with Example 1, the evaporation effect is not good due to the absence of nano-fumed silica. In the present invention, PDMS, carbon black and nano-fumed silica have a synergistic effect, combined with the adhesion effect of ethyl orthosilicate, so that the Janus foam copper evaporator of the present invention has a good evaporation effect on water.

[0078] The Janus copper foam evaporator was placed in a 3.5wt% sodium chloride solution to simulate the evaporation and desalination of seawater. The evaporation rate of the Janus copper foam evaporator in salt water is almost equal to the evaporation rate in pure water. In practical applications, the salt rejection ability of the solar seawater desalination evaporator is very important. The Janus copper foam evaporator has high thermal conductivity and large pores, which are more conducive to gradient self-cleaning. In order to verify the self-cleaning and desalination ability of the Janus copper foam evaporator of Example 1 of the present invention during the evaporation process, 3g of salt crystals were loaded on the surface of the Janus copper foam evaporator. The results are as follows Figure 5 As shown by Figure 5 It can be seen that the salt crystals of the load are in a semi-dissolved state. Since the Janus copper foam evaporator is capillary-shaped from top to bottom, forming vertically arranged microchannels, this provides enough water flux for solution flow, and the salt crystals are combined with water, and a dissolution trend has occurred. The salt concentration on the surface is always higher than the concentration of the underlying salt solution, so after the salt crystals dissolve, the capillaries allow salt ions to be transferred to the lower salt solution by diffusion and advection. After stable evaporation for 3h under 1 sunlight, the surface salt crystals of the Janus copper foam evaporator almost completely dissolve and disappear, and this self-cleaning desalination characteristic shows that the Janus copper foam evaporator has the advantage of long-term use in seawater desalination. Other embodiments have the same salt rejection ability.

[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator, characterized in that: The steps include: (1) Pre-spraying solution: PDMS, nano-fumed silica and nano-carbon material are mixed in proportion, diluted with an organic solvent, and stirred evenly to obtain a pre-spraying solution; (2) adding a binder to the pre-spraying solution and mixing the mixture evenly to obtain a spraying solution; The adhesive is ethyl orthosilicate containing a catalyst; (3) Spraying the spray solution onto one surface of a clean copper foam. Before spraying, measures need to be taken to prevent the spray solution from penetrating into another surface through the pores of the copper foam during the spraying process. After the sprayed surface is dried, the spray solution can be selectively sprayed repeatedly for multiple times. After thermal curing, a super-hydrophobic-super-hydrophilic Janus copper foam evaporator is obtained.

2. The method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The PDMS is a mixture of a PDMS prepolymer and a PDMS curing agent in a mass ratio of 10:1; the nano-carbon material is any one or more of nano-carbon black, graphene, graphene oxide, and carbon nanotubes; and the organic solvent is hexane.

3. The method for preparing a super-hydrophobic-super-hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The mass ratio of the PDMS, the nano-gas-phase silica and the nano-carbon material is 10:1:

5.

4. The method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The particle size of the nano-gas-phase silicon dioxide is 20-50 nm, the particle size of the nano-carbon material is 200-500 nm; and the pore size of the foam copper is 30-50 μm.

5. The method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The mass concentration of the pre-spraying solution is 0.05-0.18 g / mL; the volume ratio of the pre-spraying solution to the adhesive is (45-150):

1.

6. The method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The measure is to extrude the foam copper into the soft fiber so that only one surface of the foam copper is exposed, or the measure is to seal the foam copper surface that does not need to be sprayed with adhesive tape.

7. The method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The volume ratio of the catalyst to the tetraethyl orthosilicate is 1:1; the catalyst is dibutyltin dilaurate.

8. The method for preparing a super hydrophobic-super hydrophilic Janus copper foam evaporator according to claim 1, characterized in that: The thermal curing temperature is 80-120° C. and the curing time is 2-6 hours.

9. A super-hydrophobic-super-hydrophilic Janus copper foam evaporator prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of a super-hydrophobic-super-hydrophilic Janus copper foam evaporator prepared according to the preparation method according to any one of claims 1 to 8 in seawater desalination evaporation.